2001
DOI: 10.1086/321970
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Sepiapterin Reductase Gene Cause a Novel Tetrahydrobiopterin-Dependent Monoamine-Neurotransmitter Deficiency without Hyperphenylalaninemia

Abstract: Classic tetrahydrobiopterin (BH(4)) deficiencies are characterized by hyperphenylalaninemia and deficiency of monoamine neurotransmitters. In this article, we report two patients with progressive psychomotor retardation, dystonia, severe dopamine and serotonin deficiencies (low levels of 5-hydroxyindoleacetic and homovanillic acids), and abnormal pterin pattern (high levels of biopterin and dihydrobiopterin) in cerebrospinal fluid. Furthermore, they presented with normal urinary pterins and without hyperphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
175
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 196 publications
(182 citation statements)
references
References 42 publications
5
175
0
2
Order By: Relevance
“…These enzymes play an important role in the metabolism of aromatic amino acids and monoamine neurotransmitter biosynthesis (Fig. 1B) (1). Previous reports have shown that BH4 deficiency is associated with numerous metabolic syndromes and neuropsychological disorders (2,3).…”
Section: Tetrahydrobiopterin (Bh4)mentioning
confidence: 87%
See 1 more Smart Citation
“…These enzymes play an important role in the metabolism of aromatic amino acids and monoamine neurotransmitter biosynthesis (Fig. 1B) (1). Previous reports have shown that BH4 deficiency is associated with numerous metabolic syndromes and neuropsychological disorders (2,3).…”
Section: Tetrahydrobiopterin (Bh4)mentioning
confidence: 87%
“…Mammalian SPRs have been a focus of study in recent years. The major symptoms of SPR deficiency are mental retardation, dystonia, spasticity, and movement disorder (1,3). Diagnosis and therapy of SPR and/or BH4 deficiency-dependent genetic diseases, such as recessive DOPA-responsive dystonia and phenylketonuria, have been developed recently (3)(4)(5).…”
Section: Tetrahydrobiopterin (Bh4)mentioning
confidence: 99%
“…A few cases of human sepiapterin reductase deficiency, a BH 4 -dependent monoamine neurotransmitter deficiency without hyperphenylalaninemia, have been described in the literature Bonafe et al, 2001). A SPR knockout mouse has been created to model human sepiapterin reductase deficiency (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated an alternative synthesis of BH4 and DH4 in Dictyostelium in the absence of SR. The alternative synthesis of BH4 in vivo was suggested to be possible by the activities of CR(s) and AR [6,7] and recently identified in human SR deficient patients [8].…”
Section: Pteridine Production By the Mutant Cellsmentioning
confidence: 99%
“…AR specifically reduces C2 0 carbonyl group and generates 1 0 -oxo-2 0 -L L-hydroxypropyl-tetrahydropterin (H4-pterin), which is further reduced to BH4 by SR. In the complete absence of SR activity, an alternative synthesis of BH4 was suggested to be possible by carbonyl reductase (CR) and AR [7] and was recently demonstrated in vivo through finding of human patients deficient in SR [8]. BH4 has two chiral carbons in its C6-side chain and therefore can exist as four different isomers.…”
Section: Introductionmentioning
confidence: 99%